2021
DOI: 10.1002/1438-390x.12080
|View full text |Cite
|
Sign up to set email alerts
|

Missing piece of top predator‐based conservation: Demographic analysis of an owl population on a remote subtropical island

Abstract: Top predators are frequently the target of conservation programs. Owls are such predators. However, previous studies of owls are biased to species occurring in temperate regions, whereas most owl species occur in tropical or subtropical regions and are understudied. Furthermore, owls are often endemic to islands and of unknown conservation status. Demographic data for such species are especially scarce although they are essential for initiating and promoting their conservation. As a case study of demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Males carry food to their mates until the middle of the nestling period, and thereafter the parents share feeding duties (Murakami et al, 2022 ; Takagi & Akatani, 2011 ). There is no significant sexual difference in annual survival rate (Sawada, Iwasaki, Inoue, et al, 2021 ). The average body mass of adult males and adult females are 88.4 and 92.2 g, respectively, showing slight reversed sexual size dimorphism (Sawada, Iwasaki, Matsuo, et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Males carry food to their mates until the middle of the nestling period, and thereafter the parents share feeding duties (Murakami et al, 2022 ; Takagi & Akatani, 2011 ). There is no significant sexual difference in annual survival rate (Sawada, Iwasaki, Inoue, et al, 2021 ). The average body mass of adult males and adult females are 88.4 and 92.2 g, respectively, showing slight reversed sexual size dimorphism (Sawada, Iwasaki, Matsuo, et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the survival rate, we constructed a CJS model with survival rate modeled by five fixed effects (Year, Sex, Age, Culmen length, Wing length) and detection probability modeled by two fixed effects (Sex, Researcher; Sawada, Iwasaki, Inoue, et al, 2021 ). To consider sex‐dependency of the effect of body size, regression coefficients for body size (Culmen length, Wing length) were modeled to be sex‐dependent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic data are essential for initiating and promoting their conservation. The last image illustrates an integrated population model, which was applied to monitoring data of the Ryukyu Scops Owl population on Minami-daito Island, Japan (Sawada et al, 2021). The authors revealed the long-term averages of annual survival rates, annually fluctuating sex ratio, population size, and population growth rate.…”
Section: Cover Page Photos and Figuresmentioning
confidence: 99%